2010
DOI: 10.1144/sp330.11
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Late Cretaceous tectonic processes on sedimentation patterns along the northeastern Arabian plate margin (Fars Province, SW Iran)

Abstract: During the Late Cretaceous the northeastern margin of the Arabian plate (Zagros–Fars Area) was characterized by significant variations in sedimentary facies, sedimentation patterns and accommodation space, and by shifting depocentres. A succession of events recording the evolution of the region from a passive to an active margin is documented by the study of eight outcrop sections and one well. This new study uses new age dating (benthic and planktonic foraminifers, nannoplankton and radiolarian biozonations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Stoneley, 1990;Alavi, 1994;Hessami et al 2001;Mohajjel, Fergusson & Sahandi, 2003;Agard et al 2005Agard et al , 2006Mouthereau et al 2007;Piryaei et al 2010). However, most of these reconstructions are qualitative and thus difficult to compare with our results.…”
Section: B Comparison With Previous Qualitative Arabian Margin Recmentioning
confidence: 69%
See 1 more Smart Citation
“…Stoneley, 1990;Alavi, 1994;Hessami et al 2001;Mohajjel, Fergusson & Sahandi, 2003;Agard et al 2005Agard et al , 2006Mouthereau et al 2007;Piryaei et al 2010). However, most of these reconstructions are qualitative and thus difficult to compare with our results.…”
Section: B Comparison With Previous Qualitative Arabian Margin Recmentioning
confidence: 69%
“…Recent studies in the external Zagros have shown that the earliest deformation events related to the obduction of Neo-Tethyan oceanic crust were not only recorded in the hinterland of the chain but also in several anticlines of the external portions of the Zagros Fold Belt Piryaei et al 2010;Saura et al 2011). In addition, the onset of the main deformation event (continental collision) was found to be older than previously thought (e.g.…”
Section: Introductionmentioning
confidence: 85%
“…Although radiolarian-rich sediments could be observed on continental margin or shallow marine platforms (e.g. Ellis & Baumgartner 1995, Danelian et al 1997) during the upwelling of cold and nutrient-rich waters (Piryaei et al 2010), the fossil record and the absence of euphotic components suggest basinal conditions (Cosovic et al 2004. These sediments are therefore interpreted as representing intra-shelf basin deposits (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These sediments are therefore interpreted as representing intra-shelf basin deposits (e.g. Piryaei et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation